Aplikatif Pemikiran Pendidikan Ibnu Khaldun - Aminudin, Aminudin (Pusat Studi Pendidikan Kreatifitas Anak Wadas Kelir Purwokerto, 2020)
Studying past Islamic education figures is something that is still considered saturating. But basically, studying history is not to always be applied, but as a material consideration in the present. One of them was Ibn Khaldun whose full name was Muhammad bin Muhammad bin Hasan bin Jahir bin Muhammad bin Ibrahim bin â€˜Abd al-Rahman bin Khalid who later became known as Khaldun. The most famous work is KitÄb al-'Ibar wa DÄ«wÄn al-Mubtada 'wa al-Khabar fÄ« AyyÄm al-Arb wa al-'Ajam wa al-Barbar wa Man' Ä€sharahum min DzawÄ« al-SulthÄn al-Akbar which contains sample books examples and records of the origins and events of the Arabian, Persian, Barbarian and contemporaries and those who have great powers, or often abbreviated as the book al-'Ibar only. Ibn Khaldun classifies his thoughts on education as in the Muqaddimah into four namely: definition and purpose of education, educators, students, education methods and materials.